Sosialisasi Legalitas Usaha dalam Pengembangan UMKM di Desa Kedungdalem Kabupaten Probolinggo - Muhammad Faiz Subhanulfikri; Ratih Mukti Azhar (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Businesses that are recognized by society and the government are businesses that have legality because legality is the most important element in a business and is also an identity that legalizes or legalizes a business entity. The problem that will be faced in this dedication to the community is a lack of insight and views on the legality of business, especially in MSMEs. The majority of people in Kedungdalem Village, Dringu District, Probolinggo Regency, are micro, small and medium businesses such as chip businesses, herbal medicine businesses, catering businesses, cooking spices, wet snacks, pastries, and other businesses. The purpose of this service activity is to provide business legality socialization for MSMEs in Kedungdalem Village. The activity implementation technique consists of several levels, namely preparation, implementation, and evaluation. The results of community service activities are that business actors experience an increased understanding of business legality, the benefits of business legality, the consequences of not having business legality, and also business actors having a Business Identification Number (NIB)..